A two-stage optimization configuration model for multi-type flexible resource considering spatiotemporal response characteristics - Liang, Yan; qi, xin; Bai, Xiping; Zhou, Ming (Frontiers in Energy Research, 2024)
As China gradually transitions towards a low-carbon energy structure, the proportion of grid-connected new energy sources like wind and solar power continues to increase. To ensure the safe and reliable operation of the power system while meeting the capacity planning for future new energy installations, there is a need for flexible resources with corresponding adjustment capabilities in the power system. In response to this situation, this paper presents an optimization model for the allocation of multiple types of flexible resources that takes into account spatiotemporal response characteristics. Firstly, a flexibility evaluation model is developed based on spatial and temporal response characteristics. Flexibility evaluation indices, such as flexibility average deficit and flexibility coverage index, are constructed. These indices are used for screening nodes with inadequate flexibility in the power system and analyzing the flexibility adequacy at various nodes. Next, the adjustment characteristics of multiple types of flexible resources are analyzed, and a model for their adjustment capabilities is established. Finally, by considering constraints based on time flexibility evaluation indices, a two-stage optimization model for flexible resource allocation is constructed. This model leverages the multiscale matching characteristics between flexibility resources and the fluctuation patterns of new energy sources to guide the allocation of flexible resources at nodes with insufficient flexibility. The effectiveness and applicability of the proposed flexible resource allocation method are validated using the IEEE 9-node system.